1997
DOI: 10.1007/bf02778078
|View full text |Cite
|
Sign up to set email alerts
|

Type-1 insulin-like growth factor receptor reexpression in the malignant phenotype of SV40-T-immortalized human prostate epithelial cells enhances apoptosis

Abstract: The authors have previously shown that the type 1 insulin-like growth factor receptor (IGF-1R) is decreased in the transformation from benign to malignant human prostate epithelial cells in vivo. Further, in a well-described human SV40-T immortalized human epithelial cell system beginning with the immortalized, but rarely tumorigenic P69SV40-T cell line, to the highly tumorigenic and metastatic M12 subline, there is a similar decrease in IGF-1R number from 2.0 x 10(4) receptors per cell to 1.1 x 10(3) receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…IGFIR initially was evaluated as a potential dependence receptor because its targeted disruption in transgenic mice was shown to lead to an increase in neuronal density in the spinal cord and brainstem (25) and because its overexpression was shown to inhibit tumor formation and induce cell death (26)(27)(28). Membrane targeting was required for cell death induction by IGFIR, because omission of the myristylation site in the IG-FIR-IC construct destroyed its ability to induce cell death (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IGFIR initially was evaluated as a potential dependence receptor because its targeted disruption in transgenic mice was shown to lead to an increase in neuronal density in the spinal cord and brainstem (25) and because its overexpression was shown to inhibit tumor formation and induce cell death (26)(27)(28). Membrane targeting was required for cell death induction by IGFIR, because omission of the myristylation site in the IG-FIR-IC construct destroyed its ability to induce cell death (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the expression of IGFIR was decreased in prostate cancer (38), and its reexpression in immortalized human prostate cells inhibited the malignant phenotype (26). A potential role for IGFIR in developmental cell death was suggested by the phenotype of IGFIR-null mice, which includes a higher neuronal density in the brainstem and spinal cord (25).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, our results are in line with evidence that the IGF-1R/IGF-1 axis is not an oncogenic driver in primary PCa. Plymate et al demonstrated that restored expression of IGF-1R in malignant prostate cells slowed down growth both in vitro and in vivo [33], while an in vivo study by Sutherland et al showed that conditional prostate-specific IGF-1R knockout caused cell proliferation, hyperplasia and the emergence of aggressive PCa when p53 activity was compromised [34]. Furthermore, Massoner et al demonstrated that the IGF axis is up-regulated during normal epithelial differentiation in vitro [35].…”
Section: Discussionmentioning
confidence: 99%
“…12,37 In keeping with this emerging role, a potential function of IGFIR as a tumor suppressor was suggested by findings that the expression of IGFIR was decreased in prostate cancer, 38 and its reexpression in immortalized human prostate cells inhibited the malignant phenotype. 39 A potential role for IGFIR in developmental cell death could explain part of the phenotype of IGFIR-null mice, in which a higher neuronal density in the brainstem and spinal cord was observed. 40 Engagement of at least two signaling pathways triggered by IGFIR, the MAPK/ERK and JNK pathways, occurred in paraptosis.…”
Section: Discussionmentioning
confidence: 99%